2012
DOI: 10.1093/eurpub/cks118
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and risk of early retirement. The HUNT study

Abstract: Background: We explore the possible consequences of measured hearing impairment (HI) and perceived hearing difficulties for early retirement in a large population-based study. Furthermore, we study whether having a part-time position was associated with measured HI and perceived hearing difficulties in the same population. Methods: This study included 25 740 persons from the Nord-Trøndelag Health Study (HUNT) aged 20–54 years at baseline in HUNT1 (1984–1986) who also participated in the follow up, HUNT2, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 22 publications
4
31
0
2
Order By: Relevance
“…We believed that retirement could have an effect on tinnitus severity as tinnitus patients could find tinnitus is very disruptive when they spend more time in silence at home. The association between hearing impairments and retirement was identified, which found that the incidence of retirement is significantly higher in hearing impairment population comparing to normal hearers [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…We believed that retirement could have an effect on tinnitus severity as tinnitus patients could find tinnitus is very disruptive when they spend more time in silence at home. The association between hearing impairments and retirement was identified, which found that the incidence of retirement is significantly higher in hearing impairment population comparing to normal hearers [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…5,10 Although the prior report implicated noise from the high-speed surgical drill as the cause of HFHL following MVD, we conducted this study to examine the incidence of HFHL, with an emphasis on retractorless MVD for treatment of HFS.…”
mentioning
confidence: 99%
“…Helvik et al 2012;Hogan et al 2009;Friberg et al 2012;Nachtegaal et al 2012;Pierre et al 2012) daraufhin, dass bei Menschen mit einer Hörbeeinträchtigungen eine niedrigere Erwerbsbeteiligung, höhere Arbeitslosenquoten und höhere Frühberentungsquoten festzustellen sind als bei Menschen ohne Hörbeeinträchtigungen. Besonders davon betroffen zeigen sich dabei die höheren Altersgruppen.…”
Section: Arbeitsleben Und Hörbeeinträchtigungenunclassified
“…Besonders davon betroffen zeigen sich dabei die höheren Altersgruppen. So ergab sich bei der norwegischen HUNT (Hearing loss and risk of early retirement) Studie (Helvik et al 2012 …”
Section: Arbeitsleben Und Hörbeeinträchtigungenunclassified